Marker assisted forward breeding to combine multiple biotic-abiotic stress resistance/tolerance in rice - Dixit, Shilpi; Singh, Uma Maheshwar; Singh, Arun Kumar; Alam, Shamshad; Venkateshwarlu, Challa; Nachimuthu, Vishnu Varthini; Yadav, Shailesh; Abbai, Ragavendran; Selvaraj, Ramchander; Devi, M. Nagamallika; Ramayya, Perumalla Janaki; Badri, Jyothi; et al. (Springer, 2020)
Unfavorable climatic changes have led to an increased threat of several biotic and abiotic stresses over the past few years. Looking at the massive damage caused by these stresses, we undertook a study to develop high yielding climate-resilient rice, using genes conferring resistance against blast (Pi9), bacterial leaf blight (BLB) (Xa4, xa5, xa13, Xa21), brown planthopper (BPH) (Bph3, Bph17), gall midge (GM) (Gm4, Gm8) and QTLs for drought tolerance (qDTY1.1 and qDTY3.1) through marker-assisted forward breeding (MAFB) approach. Result Seven introgression lines (ILs) possessing a combination of seven to ten genes/QTLs for different biotic and abiotic stresses have been developed using marker-assisted selection (MAS) breeding method in the background of Swarna with drought QTLs. These ILs were superior to the respective recurrent parent in agronomic performance and also possess preferred grain quality with intermediate to high amylose content (AC) (23–26%). Out of these, three ILs viz., IL1 (Pi9+ Xa4+ xa5+ Xa21+ Bph17+ Gm8+ qDTY1.1+ qDTY3.1), IL6 (Pi9+ Xa4+ xa5+ Xa21+ Bph3+ Bph17+ Gm4+ Gm8+ qDTY1.1+ qDTY3.1) and IL7 (Pi9+ Xa4+ xa5+ Bph3+ Gm4+ qDTY1.1+ qDTY3.1) had shown resistance\tolerance for multiple biotic and abiotic stresses both in the field and glasshouse conditions. Overall, the ILs were high yielding under various stresses and importantly they also performed well in non-stress conditions without any yield penalty. Conclusion The current study clearly illustrated the success of MAS in combining tolerance to multiple biotic and abiotic stresses while maintaining higher yield potential and preferred grain quality. Developed ILs with seven to ten genes in the current study showed superiority to recurrent parent Swarna+drought for multiple-biotic stresses (blast, BLB, BPH and GM) together with yield advantages of 1.0 t ha− 1 under drought condition, without adverse effect on grain quality traits under non-stress.